An updated overview of anticancer effects of alternariol and its derivatives: underlying molecular mechanisms - Islam, Muhammad Torequl; Martorell, Miquel; González-Contreras, Carlos; Villagran, Marcelo; Mardones, Lorena; Tynybekov, Bekzat; Docea, Anca Oana; Abdull Razis, Ahmad Faizal; Modu, Babagana; Calina, Daniela; Sharifi-Rad, Javad (Frontiers in Pharmacology, 2023)
Alternariol is a toxic metabolite of Alternaria fungi and studies have shown multiple potential pharmacological effects. To outline the anticancer effects and mechanisms of alternariol and its derivatives based on database reports, an updated search of PubMed/MedLine, ScienceDirect, Web of Science, and Scopus databases was performed with relevant keywords for published articles. The studies found to suggest that this mycotoxin and/or its derivatives have potential anticancer effects in many pharmacological preclinical test systems. Scientific reports indicate that alternariol and/or its derivatives exhibit anticancer through several pathways, including cytotoxic, reactive oxygen species leading to oxidative stress and mitochondrial dysfunction-linked cytotoxic effect, anti-inflammatory, cell cycle arrest, apoptotic cell death, genotoxic and mutagenic, anti-proliferative, autophagy, and estrogenic and clastogenic mechanisms. In light of these results, alternariol may be one of the hopeful chemotherapeutic agents.